A Small State’s Security Strategy in a Changing World – Republic of Moldova Case Study - Stănescu Marina (Scientific Bulletin)
The theory of international relations has traditionally focused on the behavior and strategies of great powers, often marginalizing the unique challenges and opportunities faced by small states in the international system. This article explores the foreign policies of small states through the lens of key international relations theories. It argues that while small states are often seen as reactive or constrained by the dominance of larger powers, they can exercise significant agency through strategic alignment, multilateral engagement, and normative influence. By leveraging international institutions, economic diplomacy, and soft power, small states can enhance their security and achieve their foreign policy objectives despite their limited material resources. This article provides insights into the broader role of small states in the international system, using the Republic of Moldova as a case study to highlight how neutrality can be a proactive and effective foreign policy in a complex global environment. This analysis contributes to a deeper understanding of how small states can play an active and influential role in international relations.